(3GdMGTjI Ydi eYGde GdOjfs - (3GdeGRfOQGfj, GdCUagGfj, MSGe GdOjf, eMeO UGdM Hf CMeO, J (B1081 (3g`s ((3MSjf Hf edG cGXe GdcjdGfjs)
(3ChdgG (B:s
(3fMeOc Gddge jG ef NdbfG hde fc TjFG ePchQG(B...(3CeG HYO(B...(3Ef HYV CNdGFj Mjf QCi eG YdbJg Ydi eYGde GdOjf(B...(3SCdfj Cf CMQQ dge ahGFOg(B...s
(3BNQgG (B:s
(3dCfG fbhd djSJ GdHdGZI HeLQO MSf GdJCdja aj GdeYfi Hd dGHO ajgG ef eQGYGI MSf GdJQcjH aj GdfXe(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B:(3L(B6(3,U(B151(3,Qbe(B1150s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs